2020
DOI: 10.1063/5.0026564
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of photon upconversion performance and antisolvent processing in thin-film halide perovskite-sensitized triplet–triplet annihilators

Abstract: Note: This paper is part of the JCP Special Topic on Up-and Down-Conversion in Molecules and Materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…To‐date, all reported bulk perovskite‐sensitized TTA‐UC devices are fully solution‐processed by either spin‐coating the organic annihilator layer onto the perovskites or directly incorporating the annihilator into the antisolvent, [ 11,12,18–21 ] which poses an obstacle to unravelling the detailed photophysics of perovskite‐sensitized upconversion. Perovskites are notoriously sensitive to solvent exposure and fabrication conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To‐date, all reported bulk perovskite‐sensitized TTA‐UC devices are fully solution‐processed by either spin‐coating the organic annihilator layer onto the perovskites or directly incorporating the annihilator into the antisolvent, [ 11,12,18–21 ] which poses an obstacle to unravelling the detailed photophysics of perovskite‐sensitized upconversion. Perovskites are notoriously sensitive to solvent exposure and fabrication conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The same properties which make perovskite materials uniquely qualified as the active layer in a PV, enable triplet sensitization through a freecharge carrier process. [8][9][10][11][12][13][14][15] Photon UC in general describes the process of increasing the emitted photon energy upon photon absorption. [16][17][18][19][20] To comply with energy conservation laws, this process requires the combination of the energy of multiple absorbed photons to generate a single high energy excited state.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, this is counteracted by a higher absorption of the FA-rich perovskites, which we have previously shown to exhibit higher UC photoluminescence (PL) intensities than their MA-rich counterparts. Other important factors to consider are the native PL lifetimes and resulting carrier diffusion lengths, 14 Fermi levels 24 and interfacial band bending, 11,26 which can all influence the number of charges extracted at the perovskite/rubrene interface. We have previously shown that one of the current limitations of the perovskite/rubrene UC system is incomplete charge extraction, which can be attributed to the lack of driving force for electron transfer, a limited driving force for charge transport to the interface, localized trap states or charge transfer states mediating the charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, the exact mechanism of triplet sensitization is still unclear. [30][31][32][33] Understanding the fundamental mechanism of triplet sensitization at the perovskite/organic interface will be the key in further improving perovskite-based UC, as it will unlock engineering pathways to further increase the device performance.…”
mentioning
confidence: 99%
“…Particularly, it emphasizes that only a small fraction of free charges created upon photoexcitation are successfully extracted and return upconverted photons despite the long-lived nature of the free carriers in the perovskite, which should allow a large number of charges to be extracted within their lifetime. 23,28 Possible causes include localized states mediating electron and hole transfer and limiting the number of generated triplet states 30,31 and short-lived transient states (e.g. hot carriers) being involved in the triplet generation process.…”
mentioning
confidence: 99%